Theoretical Study about the Effect of Halogen Substitution on the Reactivity of Antitumor 3-Formylchromones and Their Free Radicals - Maximiliano Martínez-Cifuentes; Boris Weiss-López; Ramiro Araya-Maturana (Journal of Chemistry)
The mandatory presence of a chlorine atom on the aromatic ring of 6-hydroxy-3-formyl angular chromones, on the respiration inhibition of mammary carcinoma mouse, is explained through a computational study of these compounds. This study analyzes the reactivity of the neutral molecules and their free radicals, in gas phase and with water solvation, incorporated by the polarizable continuum medium (PCM) approach. Electrophilic reactivities were evaluated using Fukui (f+) and Parr (P+) functions. The stabilities of radical species formed by the abstraction of a hydrogen atom from the O-H bond were evaluated by bond dissociation enthalpy (BDE) and spin density (SD) calculations. This study has potential implications for the design of chromone analogues as anticancer compounds.